The Christians of Phrygia from Rome to the Turkish Conquest - Mitchell, Stephen, (Ancient Judaism and Early Christianity ;, 2023)
The towns and villages of Phrygia, a predominantly rural region of inner Asia Minor, provide richer documentation of their early Christian communities than any other part of the Roman empire. This includes the earliest lengthy Christian funerary text, coin types depicting Noah and the Flood introduced by Christians at the Phrygian emporium of Apamea, the famous 'Christians for Christians' inscriptions, and more than a hundred other pre-Constantinian grave monuments, The abundant evidence for the Christian presence up the Turkish invasions throws new light on continuity between Late Antiquity and the Middle Byzantine period, and on the warfare between the Byzantines and Turks in the 11th century. This is the first exhaustive regional study since 1897.